Vegetation dynamics in north-western Mediterranean regions: Instability of the Mediterranean bioclimate - De Beaulieu, J.-L.; Miras, Y.; Andrieu-Ponel, V.; Guiter, F. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Pollen and plant macrofossil records from a selection of sites in Spain, France and Italy are used to explore the origin and the development of the Mediterranean vegetation. The role of evergreen and summergreen taxa is discussed. The expansion of sclerophyllous trees during the Pleistocene interglacials is well correlated with the orbital forcing. During the Holocene, the large number of data illustrates latitudinal and longitudinal differences in vegetation dynamics. Multidisciplinary studies identify short terms climatic fluctuations. The debate is still open between those who attribute an increase of sclerophyllous forests during the late Holocene to a trend toward aridity and those who consider this dynamic as human-induced.
doi: 10.1080/11263500500197858doi: 10.1080/11263500500197858The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: human impact; Mediterranean ecosystems; palaeoclimates; palynology; review

The Holocene at Lac de Creno, Corsica, France: a key site for the whole island (New Phytologist, 1999)
Two Holocene lake sequences from Lac de Creno, Corsica were analysed on the basis of 119 pollen spectra and with the support of 13 14C-calibrated dates. The lower part of one of these sequences, corresponding to the late- glacial period, has been published previously. The first third of the Post-glacial is characterized by very particular forest dynamics, namely the absence of a role for deciduous Quercus and Corylus, the presence of mesophilous vegetation types dominated by Taxus, and the major forest role of Erica arborea at lower and mean altitude. At about 7440 cal BP, the occurrence of a major anthropogenic action brought about significant changes in the vegetation, notably an increase of deciduous Quercus and the expansion of Quercus ilex. Later, three major human-induced events are identified: the first, at about 2290 cal BP, is the cause of a short local expansion of Abies; the second, at about 1150 cal BP, is the degradation of deciduous forests to the benefit of Fagus; the third, at about 310 cal BP, corresponds to the disappearance of Fagus and its replacement by Pinus. Pollen data indicate that Q. ilex, Abies and Fagus are not indigenous in Corsica but spread there during the Postglacial ; this probably took place at about 6980 cal BP for Q. ilex.

The late-glacial at Lac de Creno (Corsica, France): a key site in the western Mediterranean basin (New Phytologist, 1997)
The lower part (460–650 cm) of a lacustrine sequence from Lac de Creno, Corsica (1310 m) is analysed on the basis of 68 pollen spectra and with the support of 10 14C dates (including nine A.M.S. dates). This sequence, which extends from the end of the Würm to the beginning of the Postglacial, reveals a complete late-glacial. The absence of forest dynamics during the late glacial Interstadial in Corsica is a real mystery. Pollen data clearly suggest that Pinus laricio (=Pinus nigra Arnold ssp. laricio Maire) and perhaps other tree species did not exist in Corsica at that time.